Politik Hukum dalam Pengaturan Pencemaran Nama Baik di Era Digital: Analisis Putusan MK No. 105/PUU-XXII/2024 - Nur Rizkiah Hasanah; Hammamtio Hammamtio; Irena Puspa Mega (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Chapter in the Electronic Information and Transactions Law, particularly chapter 27A conjunction Chapter 45 paragraph (4) have been highlighted because they are considered open to multiple interpretations, repressive, and open up space for criminalization of freedom of expression, especially when criticism is directed at state institutions or public officials. This raises serious questions about whether the defamation article is in line with the principle of freedom of expression guaranteed by the 1945 Constitution. Defamation in Indonesian legal politics is a policy dynamic that seeks to harmonize the right to personal honor with the constitutional right to expression, so that through the Constitutional Court (MK) Decision No. In decision No. 105/PUU-XXII/2024, the Constitutional Court emphasized that the phrase